2000
DOI: 10.1111/j.1461-0248.2000.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated seedling emergence in interspecific competitive neighbourhoods

Abstract: Seed dormancy models suggest that evaluation of environmental conditions should influence the decision to germinate and that waiting for more favourable conditions may increase potential fitness. However, because rapid emergence is often positively correlated with performance and survival, an alternative strategy to accelerate the rate of emergence may increase the potential for site pre-emption. This response is more likely to be found in seasonal environments with greater potential for rapid resource depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 35 publications
6
105
0
Order By: Relevance
“…In this particular invasive species, the evidence concurs with field studies describing the importance of life-history traits and the seed biology of C. solstitialis in California in that a large proportion of seeds can germinate and frequently do so very quickly [18]. While not measured directly here, it is likely that C. solstitialis can express the phenomenon described as adaptive acceleration in competitive contexts [42]. In this study, increased germination by seeds from California was detected, and acceleration was potentially expressed via an increased relative growth rate similar to field studies [13].…”
Section: Discussionsupporting
confidence: 82%
“…In this particular invasive species, the evidence concurs with field studies describing the importance of life-history traits and the seed biology of C. solstitialis in California in that a large proportion of seeds can germinate and frequently do so very quickly [18]. While not measured directly here, it is likely that C. solstitialis can express the phenomenon described as adaptive acceleration in competitive contexts [42]. In this study, increased germination by seeds from California was detected, and acceleration was potentially expressed via an increased relative growth rate similar to field studies [13].…”
Section: Discussionsupporting
confidence: 82%
“…Variation in emergence time can potentially amplify the effect of size and reproductive hierarchies and their evolutionary consequences (Fowler 1984;Weiner 1990;Miller et al 1994;Dyer et al 2000). In our study, early germination was observed primarily in riparian sites where competition is presumably more intense.…”
Section: Patterns Of Local Adaptationmentioning
confidence: 64%
“…These over-estimates might stem from all the possible risks or factors that may select for greater bet-hedging, e.g. seed predation, interspecific competition, variable temperature, and disease [21][22][23][24][25][26][27], which aren't included in our model. Furthermore, 30 years of precipitation may not fully capture the long-term variation in precipitation that has shaped the evolution of germination timing in these species.…”
Section: Discussionmentioning
confidence: 99%